Prenatal diagnosis of fetal glutaric aciduria type 1 with rare compound heterozygous mutations in GCDH gene - Hsiu-Huei Peng; Sheng-Wen Shaw; Kuan-Gen Huang (Elsevier, 2018)
Objective: Glutaric aciduria type 1 is a rare disease, with the estimated prevalence about 1 in 100,000 newborns. GCDH gene mutation can lead to glutaric acid and 3- OH glutaric acid accumulation, with clinical manifestation of neuronal damage, brain atrophy, microencephalic macrocephaly, decreased coordination of swallowing, poor muscle coordination, spasticity, and severe dystonic movement disorder. Case report: A 22-year-old female, Gravida 4 Para 2, is pregnancy at 13 weeks of gestational age. Her first child is normal, however, the second child was diagnosed as glutaric aciduria type I after birth. She came to our hospital for prenatal genetic counselling of her fetus at 13 weeks of gestational age. We performed GCDH gene mutation analysis of maternal blood showed IVS 3 + 1 G > A heterozygous mutation, GCDH gene mutation analysis of paternal blood showed c. 1240 G > A heterozygous mutation, and the second child has compound heterozygous IVS 3 + 1 G > A and c. 1240 G > A mutations. Later, we performed amniocentesis at 16 weeks of gestational age for chromosome study and GCDH gene mutation analysis for the fetus. The fetal chromosome study showed normal karyotype, however, GCDH gene mutation analysis showed compound heterozygous IVS 3 + 1 G > A and c. 1240 G > A mutations. The couple decided to termination of pregnancy thereafter. Conclusion: Glutaric acidemia type 1 is an autosomal recessive disorder because of pathogenic mutations in the GCDH gene. Early diagnosis and therapy of glutaric acidemia type 1 can reduce the risk of neuronal damage and acute dystonia. We report a case of prenatal diagnosis of fetal glutaric aciduria type 1 with rare compound heterozygous GCDH gene mutation at IVS 3 + 1 G > A and c. 1240 G > A mutations, which provide better genetic counselling for the couples.